SOILBORNE INSECTS AS INDICATORS OF ENVIRONMENTAL QUALITY (Revista de Ciências Agroveterinárias, 2005)
Ecosystems are important for biodiversity maintenance, assuring species survival and perpetuation. The loss of environment identity promotes lack of biological diversity. Mankind actions not based on sustainable principles have damaged forests and fields due to need of increasing agricultural frontiers to enhance production to feed an increasing population. Progress in agricultural practices and technological advances of modern industrialization did not guarantee the permanence of different planet ecosystems. The diversity of these environments is threatened, as well as the balance of the chains that depend on them. In this context, the balance of soil environment can be measured by observing the population characteristics of groups of specific organisms, considered bioindicators of the alteration degree or place weakening. The most important indicators are insects because they are the most diverse group in terms of species number and due to their easy sampling process. Therefore, the diversity of soilborne-insects can be used to measure the level of environment quality and this information can be used to design measures to keep, to recover or to restore the environmental health, aiming to reach the ecosystems sustainability.
Keywords: bioindicators; soilborne-insects; ecosystems; environment degradation.